Emotional Machines: Ethics and Biases of Emotion Artificial Intelligence in Businesses and Workplaces - Jhamb, Sumeet; Ryan, Teresa (Journal of Leadership, Accountability and Ethics, 2022)
This study discusses the emerging technology of emotion artificial intelligence and its ethical implications, particularly bias, in business. Emotion AI offers potential for many fields of business, but comes with inherent concerns over privacy, security, and ethics (Dattner et al., 2019). Past studies have revealed inherent gender and racial biases in artificial intelligences in many different aspects of business (Buolamwini, 2019; Feast, 2019; Tinsley and Ely, 2018; Wellner and Rothman, 2019). The present study considers emotion AI's current capabilities, recognizes its inherent biases, and explores solutions for gender and racial biases in AI on an ongoing basis. Through the proposed collection and analysis of secondary and primary data as well as discussion of implementing proposed solutions, this paper will suggest methods to reduce bias in emotion AI.